Determination of the association between indoor and outdoor temperature in selected houses and its application: a pilot study. Issue 5 (3rd September 2021) - Asumadu-Sakyi, A. B.; Barnett, A. G.; Thai, P. K.; Jayaratne, E. R.; Miller, W.; Thompson, M. H.; Rahman, M. M.; Morawska, L.
ABSTRACT: Quantitative information on indoor temperature is important for understanding the impacts of temperature on building energy consumption, human health and comfort, however, such information is scarce. Additionally, extraction of useful information from existing indoor temperature data is hindered by varying study designs. The study aims to: simultaneously monitor indoor and outdoor temperature of selected houses and to develop a model describing their relationship; and analyse the strengths and limitations of the model towards understanding the association between indoor and outdoor temperature. Temperature sensors were installed in 15 houses in Brisbane, Australia, to monitor at intervals of 30 min over the winter of 2016. The linear mixed-effects model which we developed performed well and predicted that on average, 1°C increase in outdoor temperature resulted in an increase of 0.4°C ± 0.05°C in indoor temperature. While the sample size of the study is relatively small, our model is expected to perform with any sample sizes particularly with large sample. Application of our indoor/outdoor temperature modelling will facilitate understanding the influence of temperature on energy consumption in households and human health. Such information is imperative towards future comfortable and low energy homes.